Breastfeeding and respiratory tract infections during the first 2 years of life. Issue 2 (2nd June 2017) - Wang, Jingying; Ramette, Alban; Jurca, Maja; Goutaki, Myrofora; Beardsmore, Caroline S.; Kuehni, Claudia E.
Breastfeeding protects against respiratory tract infections (RTIs) in infants [1–3], but whether its effects persist beyond that age is not well understood. Some studies have reported that protection diminishes soon after weaning [2], while others have found that it extends until the age of 2 years [4] or more [5, 6]. It is noteworthy that many previous studies grouped RTIs broadly into upper or lower tract infections, rather than studying specific diseases [3, 7], and few adjusted adequately for confounding factors [5] or investigated a possible effect modification by sex, which had been suggested by several studies showing a stronger protection in girls [8, 9]. Breastfeeding and respiratory tract infections http://ow.ly/Isd9309JS69